PRE-RETIREMENT ANXIETY AS A PREDICTOR OF AGEING ANXIETY AMONG TERTIARY INSTITUTION WORKERS IN ANAMBRA STATE, NIGERIA - Chigozie Nkiruka , Ukaegbu (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Workers will eventually reach a point when they have to retire. The prospect of retiring can cause anxiety, apprehension, and disillusionment in some people. Intimations suggest that pre-retirement anxiety might potentiate aging concerns in individuals. Aging is a fundamental biological process that is inevitable for all living things and describes a condition of overall change in every aspect of life. In this paper, pre-retirement is assumed to be essential to age concerns among tertiary institution workers. Two hundred and fourteen employees from five public tertiary institutions in Anambra State participated in the study. The respondents comprising males (n=90) and females (n=124) were randomly pooled from different departments. They completed a self-report measure of Aging Anxiety and the Pre-retirement Anxiety Scale. The finding revealed a statistically significant, moderate positive correlation between pre-retirement anxiety and aging anxiety, r (212) = .34, p < .001, with pre-retirement anxiety explaining 23.1% of the variation in aging anxiety significant positive association between the variables. The paper extends the empirical understanding of the interrelationship between pre-retirement and aging anxieties in the workplace.